Immunoglobulin G Subclass-Specific Glycosylation Changes in Primary Epithelial Ovarian Cancer - Wieczorek, Marta; Braicu, Elena Ioana; Oliveira-Ferrer, Leticia; Sehouli, Jahid; Blanchard, Véronique (Frontiers in Immunology, 2020)
Epithelial ovarian cancer (EOC) was previously shown to be associated with glycosylation changes of total serum and total IgG proteins. However, as a majority of previous studies analyzed released glycan profiles, still little is known about IgG subclass-specific alterations in ovarian cancer. Hence, in this study we investigated EOC-related glycosylation changes of the three most abundant IgG subclasses, namely IgG1, IgG2 and IgG3 isolated from sera of 87 EOC patients and 74 age-matched healthy controls. In order to separate IgG2 and IgG3, we performed a two-step affinity purification employing Protein A and Protein G Sepharose. After tryptic digestion, IgG glycopeptides were enriched and measured by MALDI-TOF-MS. Finally, EOC-related glycosylation changes were monitored at the level of total agalactosylation, monogalactosylation, digalactosylation, sialylation, bisection and fucosylation, calculated separately for each IgG subclass. Interestingly, aside from an EOC-related increase in agalactosylation/ decrease in mono- and digalactosylation observed in all IgG subclasses, some subclass-specific trends were detected. Glycosylation of IgG1 was found to be the most strongly affected in EOC, as it exhibited the highest number of significant differences between healthy controls and EOC patients. Specifically, IgG1 was the only subclass that showed a significant decrease in sialylation and significant increase in fucosylation in EOC patients. Interestingly, IgG2 and IgG3 that were often investigated collectively in previous studies, were found to have distinct glycosylation patterns. IgG3 displayed stronger EOC-related increase in agalactosylation/ decrease in digalactosylation and was characterized by notably higher sialylation, which consequently decreased in EOC patients. In conclusion, our study indicates that IgG subclasses exhibit subtly distinct glycosylation patterns of EOC-related alterations and IgG1 and IgG3 agalactosylation show the strongest association with CA125, the routine diagnostic marker. Additionally, our results show that simultaneous analysis of IgG2 and IgG3 might lead to wrong conclusions as these two subclasses exhibit noticeably different glycosylation phenotypes.